BIOAVAILABILITY OF CURCUMIN AND METHODS OF ITS ENHANCING - N. L. Soloveva; M. S. Sokurenkova; O. A. Zypyanov (Разработка и регистрация лекарственных средств, 2019)
Curcumin is a hydrophobic polyphenolic compound of natural origin. Curcumin has a wide range of pharmacological effects. Curcumin is inherently poorly absorbed when ingested and has low bioavailability, in part due to a low rate of absorption in the intestine and, in part, due to rapid metabolism (glucuronidation), which limits its clinical use. One of the important tasks is the development of effective forms of curcumin with the aim of increasing the bioavailability of this compound. This is achieved by including curcumin in such systems as liposomes, nanoparticles, micelles, etc., formation of complexes with cyclodextrins, and the use of bio-enhancers. In particular, the use of a complex of curcumin with piperine, a known inhibitor of the glucuronization process in the liver and intestine, increased the bioavailability of curcumin several times. Combination of curcumin with phospholipids due to its incorporation into lipophilic membranes, increased its maximum concentration in comparison with an individual curcumin. Curcumin in the form of nanoparticles had a pharmacological effect at a 15-fold lower concentration than conventional curcumin.